Health Care Executive Perceptions of Hiring and Retention Practices of People With Disabilities: Results From Executive Focus Groups. (January 2021) - McDonough, Jennifer; Ham, Whitney; Brooke, Alissa; Wehman, Paul; Wright, Travis S.; Godwin, James C.; Junod, Paul; Hurst, Robin
The supply-side approach to providing services without taking into account employer practices has not been effective in achieving meaningful, competitive, and integrated employment outcomes for people with disabilities. This focus neglects the fact that disability and employment is a two-way process with businesses being accountable for such demand-side factors as establishing better hiring, retention, and advancement practices. To initiate the identification of effective employer practices, this article shares the results of two executive focus groups that were conducted in a large health care organization, across four individual hospitals, with a documented success rate of hiring and retaining people with disabilities (PWDs). The purpose of the focus groups was to explore executive perceptions of their organization's success at integrating PWDs throughout their work force. Results are explored through five identified themes: (a) organizational mission guided decision-making concerning the employment of PWDs, (b) executives living the mission through their daily inclusive behaviors led to employing PWDs, (c) organizational values were important to employing PWDs, (d) the organization benefited from employment of PWDs, and (e) employing PWDs benefited organization staff and the surrounding community. The results of these executive focus groups provide an initial glimpse into the culture and practices of a highly effective organization.